2012
DOI: 10.18553/jmcp.2012.18.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacy and Mail Order Cost and Utilization for 90-Day Maintenance Medication Prescriptions

Abstract: BACKGROUND: Pharmacy benefit management (PBM) companies promote mail order programs that typically dispense 90-day quantities of maintenance medications, marketing this feature as a key cost containment strategy to address plan sponsors' rising prescription drug expenditures. In recent years, community pharmacies have introduced 90-day programs that provide similar cost advantages, while allowing these prescriptions to be dispensed at the same pharmacies that patients frequent for 30-day quantities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…In 2007, Desai and colleagues [37] documented that about 14.5% of the US population used the internet to obtain medications or vitamins, and these individuals were more often married, white, 50-64 years old with varying levels of college education and an income of US $75,000, or more. It should be noted, mail-order pharmacies are required by certain health plans in the US, which may result in a higher number of patients using online mail pharmacies for maintenance medications [48], compared to other countries. A Hungarian survey of hospital patients has shown in which 8.4% of the respondents ordered drugs or dietary supplements online and 3.7% of the respondents are considering this option in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, Desai and colleagues [37] documented that about 14.5% of the US population used the internet to obtain medications or vitamins, and these individuals were more often married, white, 50-64 years old with varying levels of college education and an income of US $75,000, or more. It should be noted, mail-order pharmacies are required by certain health plans in the US, which may result in a higher number of patients using online mail pharmacies for maintenance medications [48], compared to other countries. A Hungarian survey of hospital patients has shown in which 8.4% of the respondents ordered drugs or dietary supplements online and 3.7% of the respondents are considering this option in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The results also indicated that the costs of generic drugs were lower and those of branded drugs were higher at retail pharmacies and that retail pharmacies had somewhat higher rates of generic substitution. Khandelwal et al (2012), in a study comparing 90-day supplies at retail and community pharmacies, also found that retail pharmacies had lower prices for generics and higher prices for branded drugs than mail order pharmacies. 18 This price difference is somewhat surprising, given that one of mail order pharmacies' cost advantages over retail pharmacies is their ability to earn large discounts from volume purchases of generic products.…”
Section: Limitationsmentioning
confidence: 98%
“…Khandelwal et al (2012), in a study comparing 90-day supplies at retail and community pharmacies, also found that retail pharmacies had lower prices for generics and higher prices for branded drugs than mail order pharmacies. 18 This price difference is somewhat surprising, given that one of mail order pharmacies' cost advantages over retail pharmacies is their ability to earn large discounts from volume purchases of generic products. A report by Martinez (2006) in The Wall Street Journal offers a possible explanation.…”
Section: Limitationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Desai and colleagues have documented that about 14.5% of the US population used the internet to obtain medications or vitamins in 2007, individuals who buy medicines online are more often married, white, 50-64 years old with some college education and an income of $75,000 or more [52]. It should be noted that mail-order pharmacies are required by certain health plans in the United States which may result in higher number of patients using mail online pharmacies for maintenance medications [61] compared to other countries. A Hungarian survey among hospital patients has showed that 8.4% of the respondents ordered drugs or dietary supplements online and 3.7% of the respondents are considering this option in the future.…”
Section: Consumers Purchasing Medicines Onlinementioning
confidence: 99%